The title 'senti' during the first Persian period - D.A. Izosimov (Ученые записки Казанского университета: Серия Гуманитарные науки)
Modern scholars have expressed divergent views on the issue of the degree of interaction between Egyptian dignitaries and the satrapy administration during the first Persian period (526–402 B.C.). However, for a correct understanding of how Egyptians cooperated with Persians, it is necessary to analyze the specific functions performed by nobles of that period and the scope of their activity. This article analyzes the mentions of the title ‘senti’ in the inscriptions on the private monuments of Egyptian dignitaries and in the demotic Story of Peteis III. It is suggested that the ‘senti’ were mostly responsible for managing priestly affairs and for accounting and control of land plots and the income from using them. In the Story of Peteis III, the ‘senti’ person also acts as the highest judicial authority settling the dispute between Peteis III and the priests of the temple of Amun of Teudjoy, as well as several other issues. Therefore, the title ‘senti’ must have been introduced during the reign of King Amasis in an attempt to curb the autonomy of priestly corporations. Persians maintained the same policy and approved the continuation of the position of ‘senti’. Due to the important role of tax collection in the economy of the Persian Empire, the appointment of Egyptian nobles to the position of ‘senti’, which is directly associated with this function, indicates that Persians allowed the local elite to access and hold some key public positions in the satrapy.